Management in Enhancing Students' Reading Interest at SMA Negeri 1 Secanggang, Langkat Regency - Muhammad Rifa’i; Azmar; Neliwati (EDUTEC : Journal of Education And Technology, 2023)
Service management is the process of optimizing human contributions, materials, and budgets to achieve the goals of a library or library management process based on management principles and theories. On the other hand, reading interest refers to the ability to read and promote a reading culture and reading habits. Through reading, students can broaden their horizons, sharpen their ideas, and enhance their creativity. This study aims to explore the planning, implementation, and evaluation of library service activities at SMA Negeri 1 Secanggang, Langkat Regency. This research is a descriptive qualitative method. Data collection was carried out through observation, interviews, and documentation. The primary data sources of the study were interviews with the school principal, library head, library staff, teachers, and students. The secondary data consisted of documents related to library service management in enhancing students' reading interest at SMA Negeri 1 Secanggang, Langkat Regency. Data analysis techniques included data reduction, data presentation, drawing conclusions, and data validity checking by comparing interview data with the research objects. The results of the study showed that library service management in enhancing reading interest at SMA Negeri 1 Secanggang, Langkat Regency, was functioning well. The planning activities started with a meeting attended by the school principal, library head, library staff, teachers, and students. The library service implementation was carried out by two library staff members who had their respective schedules and were supervised by the library head. Evaluation was conducted on the school principal, library head, library staff, teachers, and students.